An approach for theoretical estimates of bulk specific deposit in deep bed filters - Sekerdag, N; Hasar, H; Ünlü, A (Academic Publication Council, 2001)
A large number of filtration models have been proposed since the contributions of Iwasaki. All these studies have been made for a better description of the filtration model. The observations in the filtration experiments are generally restricted to the monitoring of headloss and filtrate concentration. Based on the these values, while the estimates of the absolute specific deposit are experimentally possible, the bulk specific deposit values are estimated by using headloss models or the bulk factor treated as constant. This study presents a novel approach based on the comparison of values obtained through computer programming with the experimental values. The regression process was made between the values of the bulk specific deposit obtained through the newly-developed computer program and the absolute specific deposit obtained from the experimental studies. The regression equations had the values of r = 0.984 and r = 0.992 for run 1 and 2, respectively. The factor was found as the coefficient of the independent variable. However, the coefficient of the independent variable was termed as the bulk factor.
Keywords: absolute specific deposit; bulk factor; bulk specific deposit; filtration; headloss